High frequency shoot regeneration of various cultivars of banana (Musa sp.) - Tripathi, L.; Tripathi, J.N. (Informa UK Limited, 2008)
An efficient, simple, and rapid regeneration system was established for bananas (Musa sp.) using sections of corm containing intercalary meristematic tissues as explants. Six different cultivars of banana (‘Mpologoma’, ‘Nakitembe’, ‘Mbwazirume’, ‘Pisang awak’, ‘Sukali ndiizi’, and ‘FHIA-17’) with diverse genetic constitution and ploidy levels were regenerated on Murashige and Skoog (MS) medium supplemented with 5 mgl−1 of 6-benzylaminopurine. All the cultivars showed relatively high regeneration efficiency. About 93–97% of the explants regenerated, producing, on average, 12–13 shoots from whole section and 16–19 shoots in total from quarter pieces of each section. Regeneration from intercalary meristematic tissues offers a simple, efficient method for transformation of a broad range of banana cultivars, including East African Highland bananas. KEYWOR